Breastfeeding support and barriers to women with gestational diabetes mellitus: a nationwide cross-sectional survey of hospitals in Japan - Mayumi Matsunaga; Yaeko Kataoka; Yumiko Igarashi; Toshiko Fukui; Masumi Imura; Shigeko Horiuchi (BMC, 2021)
Abstract Background Despite the benefits of breastfeeding for women with Gestational Diabetes Mellitus (GDM) and their infants, breastfeeding is less likely to be performed by this group. This study aimed to examine the current levels of implementation of breastfeeding support to women with GDM in Japan and to clarify barriers to promoting breastfeeding among this population. Methods A 25-item questionnaire was developed by the authors to investigate the current levels of implementation of breastfeeding support for women with GDM provided in hospitals, and to explore barriers for promoting breastfeeding among these women. The questionnaire was sent to all 1046 hospitals facilitating childbirth in Japan. Descriptive statistics were used to analyze the quantitative data, and content analysis was used to analyze qualitative data from the open-ended questions. Results All 296 respondents were included in this study. Regarding breastfeeding support, 95.2% of the respondents provided general information on breastfeeding to GDM women during antenatal midwife consultations. However, the benefits of breastfeeding for preventing type 2 diabetes were addressed by only 48.0%. Likewise, although follow-up services (e.g., telephone support or breastfeeding consultations) were conducted in 88.9% of hospitals, only 50.7% of hospitals informed women that breastfeeding decreases the risk of developing type 2 diabetes after GDM. Regarding barriers, seven categories and 20 subcategories about promoting breastfeeding for women with GDM were extracted and abstracted into the following three themes: Barriers associated with mother and infant, Barriers associated with health professionals, and Organizational barriers. Conclusions In Japan, most hospitals that responded provided general breastfeeding support from the antenatal to postpartum periods. However, the benefits of breastfeeding in terms of preventing the incidence of type 2 diabetes following GDM were insufficiently communicated to women with GDM. Furthermore, there were numerous barriers to promoting breastfeeding among women with GDM.